STRATEGI PENERJEMAHAN PRIMBON BETALJEMUR ADAMMAKNA: STUDI KASUS PENERJEMAHAN ANTARBAHASA SERUMPUN LINTAS KALA - Hariyanto, Sugeng; Sujono, Adiloka; Suryanto, Bambang (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2024)
Related languages may facilitate the translation as they share many features. However, when the translation is done long after the source text was written, a potential problem may arise as the target readers have been different in terms of knowledge, habit, expectations and possibly faith. Hence, appropriate translation strategies are important. This study examined the strategies of the translation of ‘Kitab Primbon Betaljemur Adammakna’, written by R. Soemodidjojo, 57th printing, 2008, into modern Indonesian done by Wibatsu, 1st printing, 1994, published by Penerbit Soemodidjojo Mahadewa. This qualitative descriptive study compared the target text (Indonesian) with the source text (Javanese) to describe the translation strategies adopted to achieve semiotic, textual, grammatical, and semantic equivalence in the textual, sentence or clause, and word levels. The sample included the topics of ‘pawukon’, tradition or ceremonies, and human physical and trait description. The findings revealed a free approach to achieve semiotic, textual, and grammatical equivalence. Free translation and 'no-translation' were employed at the clause and sentence levels. At the word level, borrowing strategies were used for cultural words, words closely related to daily life, and specific ‘primbon’ expressions. Additional information was also used inconsistently; sometimes addition is given after slash (/) or put between brackets. The findings emphasize the importance of target readers identification before translation is done. Finally, it is suggested that the translators of similar texts identify the target readers appropriately. Further research on similar topics is suggested to interview the writer and the translator if they are still alive or reachable.Kekerabatan pasangan bahasa di dalam penerjemahan dapat mendatangkan kemudahan dan juga kesulitan bagi penerjemah jika penerjemahan dilakukan lintas kala. Untuk itu pemilihan strategi penerjemahan yang tepat menjadi penting. Penelitian ini mengkaji penerjemahan Kitab Primbon Betaljemur Adammakna dari abad 19 ke dalam bahasa Indonesia modern akhir abad 20. Penelitian deskriptif kualitatif ini membandingkan teks bahasa sasaran (Indonesia) dan teks bahasa sumber (Jawa) untuk mendeskripsikan strategi penerjemahan KPBA yang terkait dengan kesepadanan semiotika, tekstual, gramatika, dan semantik. Untuk mencapai kesepadanan semiotika dan tekstual, dan gramatika, penerjemah mengambil metode bebas. Penerjemahan bebas menerjemahkan dan juga ‘tidak menerjemahkan’ unit-unit penerjemahan tingkat klausa atau kalimat. Dalam hal semantik Pada tingkat kata penerjemah menerapkan strategi pinjaman untuk (a) kata konsep khas budaya Jawa, (b) kata yang sangat akrab dengan kehidupan sehari-hari orang Jawa, dan (c) ungkapan khas primbon. Selain itu, penambahan keterangan juga sering digunakan dengan cara yang kurang konsisten, kadang keterangan ditambahkan setelah garis miring atau di dalam kurung; dan tambahan keterangan ini bisa bahasa sumber, bahasa sasaran dan bahkan bahasa ketiga (Inggris). Temuan penelitian ini menekankan perlunya pengidentifikasian pembaca sasaran sebelum kerja terjemahan dimulai. Akhirnya disarankan agar penerjemah naskah serupa mengidentifikasi pembaca sasaran dengan lebih baik dan peneliti selanjutnya disarankan untuk menambah metode pengumpulan data dengan wawancara.Related languages may facilitate the translation as they share many features. However, when the translation is done long after the source text was written, a potential problem may arise as the target readers have been different in terms of knowledge, habit, expectations and possibly faith. Hence, appropriate translation strategies are important. This study examined the strategies of the translation of ‘Kitab Primbon Betaljemur Adammakna’, written by R. Soemodidjojo, 57th printing, 2008, into modern Indonesian done by Wibatsu, 1st printing, 1994, published by Penerbit Soemodidjojo Mahadewa. This qualitative descriptive study compared the target text (Indonesian) with the source text (Javanese) to describe the translation strategies adopted to achieve semiotic, textual, grammatical, and semantic equivalence in the textual, sentence or clause, and word levels. The sample included the topics of ‘pawukon’, tradition or ceremonies, and human physical and trait description. The findings revealed a free approach to achieve semiotic, textual, and grammatical equivalence. Free translation and 'no-translation' were employed at the clause and sentence levels. At the word level, borrowing strategies were used for cultural words, words closely related to daily life, and specific ‘primbon’ expressions. Additional information was also used inconsistently; sometimes addition is given after slash (/) or put between brackets. The findings emphasize the importance of target readers identification before translation is done. Finally, it is suggested that the translators of similar texts identify the target readers appropriately. Further research on similar topics is suggested to interview the writer and the translator if they are still alive or reachable.